2002
DOI: 10.1021/bi0267339
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric Binding Properties of a Monoclonal Antibody and Its Fab Fragment

Abstract: Detailed equilibrium binding studies were conducted on a monoclonal antibody directed against Pb(II) complexed with a protein conjugate of diethylenetriaminepentaacetic acid (DTPA). Binding curves obtained with DTPA and a cyclohexyl derivative of DTPA in the presence and absence of metal ions were consistent with the anticipated one-site homogeneous binding model. Binding curves obtained with aminobenzyl-DTPA or its complexes with Ca(II), Sr(II), and Ba(II) were highly sigmoidal, characterized by Hill coeffici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…The cross-reactivity for several metal ions including Cd 2+ , Pb 2+ , Hg 2+ , Zn 2+ , Na + , Ca 2+ , Fe 3+ , Mg 2+ , Mn 2+ , Cu 2+ , Al 3+ , Co 2+ , Cr 2+ , Ni 2+ , Sn 2+ , or K + was tested using the DC-ELISA [15,16]. Metal ions with different concentrations which ranged from 0.01 to 10 5 μg/L were mixed with 5 mM EDTA overnight to form hapten metal chelate.…”
Section: Determination Of Cross-reactivitymentioning
confidence: 99%
“…The cross-reactivity for several metal ions including Cd 2+ , Pb 2+ , Hg 2+ , Zn 2+ , Na + , Ca 2+ , Fe 3+ , Mg 2+ , Mn 2+ , Cu 2+ , Al 3+ , Co 2+ , Cr 2+ , Ni 2+ , Sn 2+ , or K + was tested using the DC-ELISA [15,16]. Metal ions with different concentrations which ranged from 0.01 to 10 5 μg/L were mixed with 5 mM EDTA overnight to form hapten metal chelate.…”
Section: Determination Of Cross-reactivitymentioning
confidence: 99%
“…2). In addition, the resulting Hill coefficient (n  =  1.68) was greater than 1 which also indicated positive cooperativity (n  =  1 signifies independent binding) [39].…”
Section: Resultsmentioning
confidence: 99%
“…This steeper slope can only be explained by use of a positive cooperativity model. In the positive cooperativity model, the binding of HB-EGF to one monoclonal antibody binding site causes the affinity of the second binding site of the antibody to increase [39]. Hence, a positive cooperativity equilibrium model was used to fit the dual-curve titration data which provided an improved fit to the dual curve data set, yielding an effective K D  =  1.50 pM (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies have shown that it is possible for IgG antibodies to display cooperativity in binding to antigens that enhances their interaction affinity 46–48. Monoclonal antibodies have also been shown to exhibit allosteric binding phenomena in the presence of appropriate binding partners and solution conditions 49…”
Section: Discussionmentioning
confidence: 99%